Spectral analysis of discrete fourier transform by using lab view - Muhammad Zilfikri Bin Zulkifli (2023)
Spectral Analysis of Discrete Fourier Transform (DFT) by Using LabVIEW is an approach by the author to implement the application of Discrete Fourier Transform (DFT) inside Lab View (Laboratory Virtual Instrumentation Engineering Workbench) software. Since, this software had been used by millions of engineers to develop sophisticated measurement, test, and control systems by using intuitive graphical icons and wires that resemble a flowchart, therefore the purpose of this project is to perform the signal analysis of Discrete Fourier Transform (DFT) for a better understanding of the subject Signal Analysis.